EVALUATION OF THE EFFECTIVENESS OF THE COLLEGIATE SYSTEM OF ADMINISTRATION IN COLLEGES OF MEDICINE IN NIGERIAN FEDERAL UNIVERSITIES (2012)
The collegiate system of administration was introduced into the Nigerian university system to ensure synchronization, decentralization and democratization of operations and devolution of powers. It is expected to aid the process of decision making and implementation as against the bureaucratic problems associated with the faculty system of administration. In spite of these advantages, the collegiate system in Nigeria universities is practised only in the colleges of medicine. Even in these colleges, little priority has been given to independent assessment of the system. This study, therefore, evaluated the effectiveness of the collegiate system of administration in Colleges of Medicine in Nigerian Federal Universities. The study adopted survey research design. Two thousand, two hundred and twenty-eight respondents consisting of 385 management, 748 academic, and 1095 non-academic members of staff were selected using stratified random sampling technique from the Universities of Ibadan, Benin and Nsukka. Collegiate System of Administration Assessment Scale with six sub-scales: Decentralisation, Devolution of Powers and Delegation Scale (r = 0.73), Decision making and Implementation Scale (r = 0.69), University Image Scale (r = 0.82), Expansion of Scale of Operations Scale (r = 0.88), Coordination and Cross- Fertilisation of Disciplines Scale (r = 0.91) and Assessment of Resources Requirements Scale (r = 0.78), was used. These were complemented with nine Key Informant Interview (KII) sessions with the sampled staff. Five research questions were raised and answered. Quantitative/qualitative data were analyzed using chi square and content analysis respectively. A high percentage of respondents were of the opinion that collegiate system of administration was effective for decentralization of university operations (85%), devolution of powers (83%) and delegation of authority and responsibility (82%). Acceleration of the process of decision making and implementation accounted for (84%) coordination and cross fertilization of related disciplines (84%) and realization of the academic objectives of the universities (86%). Among the three colleges sampled, respondents from the College of Medicine, University of Ibadan were most favourably disposed to the collegiate system of administration in terms of decentralization of university operations (x2 =28.41, df = 6 p<0.05) devolution of powers (x2 =13.42, df = 6 p<0.05), acceleration of the process of decision making and implementation (x2 = 14.72 df = 6 p<0.05). The KII showed that the respondents, generally, were favourably disposed to collegiate system of administrations. Moreover, they were of the opinion that the system had impacted positively on the administration of colleges of medicine in Nigerian federal universities but that there is evidence of lack of proper understanding of the rules guiding the system. The collegiate system positively enhanced the decision making and implementation, decentralization, devolution of powers, delegation of authority, cross-fertilization of disciplines, images of universities and their colleges of medicine and the expansion of scale of their operations. Therefore, Government and the university management should ensure that every arm of the federal universities in Nigeria embrace the use of the collegiate system of administration, while the training and retraining of staff should be vigorously pursued to ensure proper effectiveness of the system.